Implementing city strategy. Managers’ perception on strategy process in the City of Tampere - Uusi-Illikainen, Taina (My University, 2017)
Strategy is an ongoing process. Strategy is a story that is told for the organization in order to drive forward. Strategy is the activity of people. It is a political declaration. For a strategy process to be successful, creating a strategic culture within organization is important. Understand implementation and making it an important part of the strategy process will enhance the commitment and engagement of the stakeholders. Strategy implementation means interpreting, adapting and communicating. The city strategy has a dualistic essence of being both a tool for the political decision makers and citizens as well as an operational tool for the city organization. In this master’s thesis the aim is to understand strategy implementation in public sector from office holder managers’ perspective by conducting a qualitative case study with narrative inquiry approach. For this study the data is collected through focused one-to-one theme interviews with ten senior and middle civil servant office holder managers in the City of Tampere. The research questions are: how do senior and middle managers comprise strategy process in the City of Tampere and what narratives are there regarding strategic management, and especially strategy implementation in the City of Tampere. The theoretical approach in this study is strategy as practice. In literature review concepts of strategy, strategy management framework and strategy in public sector are presented. The inductive content analysis method is followed in data analyzing in this study. Lacking the culture of strategic thinking and the broken chain of management result in failing the strategy implementation not succeeding. Implementation does not automatically happen from top down. Implementation is not managed and planned in writing like the strategy document is. Strategy process should be agile to answer the demands of changing environment. The structure of the city strategy process should not tie up the strategic thinking and strategic management within the organization. To get closer to citizens and employees and get them to engage in the strategy is an issue of development for the city strategy process in the future. Managers play a vital role in this, they attach the strategy to the organization and enable the strategic discussion. In strategy process managers lead the way.
Keywords: Strategy; Strategy Process; Strategic Management; Strategy as Practice; Strategy Implementation; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|